THE INFORMATION APPROACH IN THE ASPECT OF A NEW EDUCATIONAL PARADIGM - Savchuk, L. M.; Bandorina, L. M.; Savchuk, R. V. (Science and Transport Progress, 2009)
The information approach to organization of educational process in higher education institutions, which on the basis of creation of uniform educational space allows improving the quality of training of specialists and their competitiveness at the labor market, is considered.